Differential impact of Shavasana and meditation on memory scores in healthy college students: A randomized controlled study - Ranjeet Singh Bhogal; Ghanshyam Singh Thakur; Sanjay Uddhav Shete (Wolters Kluwer Medknow Publications, 2016)
Background: Yogic relaxation techniques endow its practitioners with the relaxation of Citta (i.e., mind, intellect, and ego) and freedom from psycho-physiological fatigue. Objectives: The purpose of the present study was to compare the differential impact of the guided instructions in Shavasana and meditation in supine posture on verbal, spatial, and associate memory scores. Research Design: This was a randomized controlled trial. Method: Randomly selected 45 healthy college students were equally divided into meditation group (n = 15), Shavasana group (n= 15), and control group (n = 15), with age range of 22-30 years. All individuals were assessed for total memory through Wechsler Memory Scale before and after the 30-day intervention of yoga, consisting of two types of relaxation techniques (Shavasana and meditation in supine posture). The sessions were of 30 min each for both the intervention groups for 6 days a week. Results: Results showed significant changes in memory scores among meditation and Shavasana groups as compared to the control group. Meditation group had shown a higher magnitude of change as compared to the other groups. Within-group comparison revealed significant changes in memory scores in both meditation (P < 0.001) as well as in Shavasana (P < 0.01) groups. Conclusion: This study has concluded that the guided relaxation techniques of yoga could bring a deeper relaxation at the psycho-physiological level which, in turn, could bring about a deeper impact at higher psychological levels resulting into significant improvement in verbal, spatial, and associate memory scores.